Borders & boundaries women in India's partition - Menon, Ritu.; Bhasin, Kamla 1946-. (New Delhi Kali for Women, 1998)
On the sufferings of women during the partition of India in 1947; includes personal narratives.
UCWS-2015-G-2260 donated by Edna Aquino
Keywords: Women -- India -- History; India -- History -- Partition, 1947.